Mitophagy in Diabetic Cardiomyopathy: Roles and Mechanisms - Zheng, Haoxiao; Zhu, Hailan; Liu, Xinyue; Huang, Xiaohui; Huang, Anqing; Huang, Yuli (Frontiers in Cell and Developmental Biology, 2021)
Cardiovascular disease is the leading complication of diabetes mellitus (DM), and diabetic cardiomyopathy (DCM) is a major cause of mortality in diabetic patients. Multiple pathophysiologic mechanisms, including myocardial insulin resistance, oxidative stress and inflammation, are involved in the development of DCM. Recent studies have shown that mitochondrial dysfunction makes a substantial contribution to the development of DCM. Mitophagy is a type of autophagy that takes place in dysfunctional mitochondria, and it plays a key role in mitochondrial quality control. Although the precise molecular mechanisms of mitophagy in DCM have yet to be fully clarified, recent findings imply that mitophagy improves cardiac function in the diabetic heart. However, excessive mitophagy may exacerbate myocardial damage in patients with DCM. In this review, we aim to provide a comprehensive overview of mitochondrial quality control and the dual roles of mitophagy in DCM. We also propose that a balance between mitochondrial biogenesis and mitophagy is essential for the maintenance of cellular metabolism in the diabetic heart.